2022
DOI: 10.3389/fmed.2022.981663
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane transplantation and conjunctival autograft combined with mitomycin C for the management of primary pterygium: A systematic review and meta-analysis

Abstract: BackgroundPterygium is a common ocular surface disease. Recurrence is the greatest concern in the treatment of pterygium. Thus, a standardized and effective treatment modality with minimal risk for complications is needed for the management of pterygium. The aim of this systematic review and meta-analysis was to evaluate different tissue grafting options, including conjunctival autograft (CAG) with mitomycin C (MMC), CAG alone, and amniotic membrane transplantation (AMT), for the management of primary pterygiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…4 A systematic review and meta-analysis found single intraoperative topical application of 0.02% MMC during excision of pterygium followed by CAG to decrease the rate of pterygium recurrence significantly to 1.4% with no severe complications. 5 The lowest recurrence rate was seen after CAG especially for larger pterygia. The higher recurrence rate after intraoperative use of MMC was probably caused by selection bias.…”
Section: Discussionmentioning
confidence: 93%
“…4 A systematic review and meta-analysis found single intraoperative topical application of 0.02% MMC during excision of pterygium followed by CAG to decrease the rate of pterygium recurrence significantly to 1.4% with no severe complications. 5 The lowest recurrence rate was seen after CAG especially for larger pterygia. The higher recurrence rate after intraoperative use of MMC was probably caused by selection bias.…”
Section: Discussionmentioning
confidence: 93%
“…Several adjuvant treatments have been evaluated in the literature to reduce the risk of pterygium recurrence after surgical removal following all the aforementioned techniques. These can include antimetabolites, such as mitomycin C (MMC) and 5-fluorouracile (5-FU), anti-vascular endothelial growth factor (bevacizumab) as cyclosporin, and the use of irradiation [ 55 , 56 , 57 ]. According to a meta-analysis by Zeng et al, the use of MMC has the lowest risk of pterygium recurrence, in both bare sclera and CAG techniques, followed by beta-radiotherapy and bevacizumab [ 56 ].…”
Section: Corneal Limbusmentioning
confidence: 99%